Inequality and Democratization : An Elite-Competition Approach - Ansell, Ben W.; Samuels, David J. (Cambridge : Cambridge University Press, 2014)
Research on the economic origins of democracy and dictatorship has shifted away from the impact of growth and turned toward the question of how different patterns of growth - equal or unequal - shape regime change. This book offers a new theory of the historical relationship between economic modernization and the emergence of democracy on a global scale, focusing on the effects of land and income inequality. Contrary to most mainstream arguments, Ben W. Ansell and David J. Samuels suggest that democracy is more likely to emerge when rising, yet politically disenfranchised, groups demand more influence because they have more to lose, rather than when threats of redistribution to elite interests are low.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).